2020
DOI: 10.1002/marc.202000402
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Polyimide Covalent Organic Frameworks

Abstract: As a subseries of the covalent organic framework (COF) material family, polyimide-based covalent organic framework (PI-COF) material, which has the advantages of high stability of polyimide, high specific surface area, and controllable pores of COF material, is expected to be a new type of porous material with potential applications. Although the development of PI-COF is in the early stages during the past decade, it has attracted extensive attention and is widely used in heterogeneous catalysis, gas separatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 57 publications
0
36
0
Order By: Relevance
“…The expected trend is that crystalline (COF) porous pPIs will have higher surface areas than their amorphous counterparts (for a comprehensive review on crystalline polyimides see Zhang et al 15 ) and is indeed apparent in the highest surface area reported for the crystalline pPI synthesised by Fang et al 9 at 2403 m 2 g -1 . This trend is observed where similar pPIs were synthesised with either amorphous or crystalline properties, with the crystalline materials having higher surface areas owing to an increase in uniformity of the pores (see Table 3).…”
Section: Amorphous Vs Crystalline Ppismentioning
confidence: 96%
“…The expected trend is that crystalline (COF) porous pPIs will have higher surface areas than their amorphous counterparts (for a comprehensive review on crystalline polyimides see Zhang et al 15 ) and is indeed apparent in the highest surface area reported for the crystalline pPI synthesised by Fang et al 9 at 2403 m 2 g -1 . This trend is observed where similar pPIs were synthesised with either amorphous or crystalline properties, with the crystalline materials having higher surface areas owing to an increase in uniformity of the pores (see Table 3).…”
Section: Amorphous Vs Crystalline Ppismentioning
confidence: 96%
“…54 Because of their large surface area and micro-/mesoporous structure, they can provide versatile platforms for separation, 55 sensing, 56 and ( photo)catalysis. 57 There are many comprehensive review papers on the design and synthesis of MOFs 58,59 and COFs 60,61 for various applications.…”
Section: General Structure and Properties Of Porous Organic Frameworkmentioning
confidence: 99%
“…In recent years, there have been many publications on polyimide materials [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. In this review, the representative progress, mainly in our laboratory, in advanced polyimide films, will be described, especially focusing on the structure and properties for electronic applications.…”
Section: Introductionmentioning
confidence: 99%